IMPROVING STUDENTS’ ENGLISH SPEAKING SKILL THROUGH STORY COMPLETION TECHNIQUE IN THE SECOND GRADE OF MADRASAH ALIYAH PONDOK PESANTREN DARUL ARQAM MUHAMMADIYAH GOMBARA MAKASSAR - Ainun Ainun; Syarifuddin Dollah; Maemuna Muhayyang (Universitas Negeri Makassar, 2023)
The research aimed to examine the effectiveness of story completion strategies in boosting the speaking abilities of students enrolled in Darul Arqam Islamic Boarding School Muhammadiyah Gombara Makassar. The Story Completion Technique served as the independent variable in this study, while the students' speaking abilities served as the dependent variable. The population of this study consisted of 117 students from class XI Darul Arqam Islamic Boarding School Muhammadiyah Gombara Makassar. The research sample consisted of 21 students from XI-IPA 2 as the experimental class and 21 students from XI-IPA 1 as the control class using purposive sampling. Researchers conducted pre-test and post-test to measure students' abilities. The data showed that there is a significant difference between the experimental class and the control class. The mean score of the pre-test of the experimental class students was (3.03) and the post-test (3.61) so the experimental class had a higher improvement than the control class with the results of the pre-test (2.93) and post-test was (3,16). Based on the results of research using story completion techniques can improve students' speaking skills which has proven the data. This makes students force themselves to be more creative and think critically to complete the story.